Analytical approaches for discriminating native lard from other animal fats - Marikkar, Nazrim; Alinovi, Marcello; Chiavaro, Emma (Italian Journal of Food Science, 2021)
Establishing the distinguishable characteristics of lard from other common animal fats might be helpful for authentication initiatives in foods and feeds. In this study, fatty acid and triacylglycerol compositions, thermal and spectroscopic characteristics of native lard (NL), respectively, were compared with those of beef tallow (BT), mutton tallow (MT), and chicken fat (CF) by using gas liquid chromatography (GLC), high-performance liquid chromatography (HPLC), and differential scanning calorimetry (DSC). GLC analysis showed that the comparison of the overall fatty acid data might not be suitable for the discrimination of different animal fats, but the use of the principal component analysis and the percent palmitic acid enrichment factor [PAEF (%)] calculations were useful. HPLC analysis showed that NL displayed a TAG profile, which was quite different from those of either BT or MT, but appeared to be closely similar to that of CF. Results of DSC thermal analysis showed that both melting and crystallization curves of NL were remarkably different from those of other animal fats.